2017
DOI: 10.1016/j.biortech.2017.04.075
|View full text |Cite
|
Sign up to set email alerts
|

Electrode and azo dye decolorization performance in microbial-fuel-cell-coupled constructed wetlands with different electrode size during long-term wastewater treatment

Abstract: Microbial-fuel-cell-coupled constructed wetlands (CW-MFCs) with various cathode layers were used for long-term azo dye wastewater treatment. Their performance was assessed using cathode diameters ranging from 20 to 27.5cm and the influence of plants at the cathode was also examined. Bioelectricity generation, ABRX3 decolorization, and chemical oxygen demand (COD) removal performances first increased and then decreased with increasing cathode diameter. The CW-MFCs with larger cathodes had an anoxic region at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Tafel slopes were obtained from linear sweep voltammetry (LSV) with -2 to 2 V vs. Ag/AgCl as the voltage range and 0.01 V s −1 as the scan rate and were used to calculate the exchange current density (I 0 ) of the 3D porous electrode (Adnan et al, 2021b;Fang et al, 2017;Mousset et al, 2016b). Electrochemical impedance spectroscopy (EIS) using the frequency range from 50,000 to 0.1 Hz and an amplitude of 10 mV was performed to characterize the working electrode/electrolyte interface using the equivalent electrical circuit (EEC) method (Mousset et al, 2016b).…”
Section: Preparation and Characterization Of The 3d Porous Electrodementioning
confidence: 99%
“…Tafel slopes were obtained from linear sweep voltammetry (LSV) with -2 to 2 V vs. Ag/AgCl as the voltage range and 0.01 V s −1 as the scan rate and were used to calculate the exchange current density (I 0 ) of the 3D porous electrode (Adnan et al, 2021b;Fang et al, 2017;Mousset et al, 2016b). Electrochemical impedance spectroscopy (EIS) using the frequency range from 50,000 to 0.1 Hz and an amplitude of 10 mV was performed to characterize the working electrode/electrolyte interface using the equivalent electrical circuit (EEC) method (Mousset et al, 2016b).…”
Section: Preparation and Characterization Of The 3d Porous Electrodementioning
confidence: 99%
“…Their results indicated this system could be used for azo dye removal with 85% efficiency. Moreover, some works combined a MFC system with wetland to remove an azo dye, and they found that in optimal conditions, the MFC system could remove a toxic dye, and generate high voltage potential (Fang et al, 2017). No previous work explained a single use of MFC system for MG removal.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been performed to treat azo dye and simultaneously generate electricity [ 175 , 176 , 177 , 178 ]. One study used a single-chamber air-cathode MFC for electrical generation from the degradation of azo dyes [ 179 ].…”
Section: Complex Substratesmentioning
confidence: 99%
“…The process enhanced the dye color removal efficiency, COD removal, and electricity generation and suggested the benefits of MFCs in biodegradation and bioelectricity generation. MFCs coupled with wetlands were also used for azo degradation [ 177 , 182 , 183 , 184 ]. In one study, at a cathode diameter of 25 cm, the highest decolourization volume of 397.64 mg L −1 was observed, whereas at a 27.5 cm diameter, a CD max of 0.539 A m −2 was recorded.…”
Section: Complex Substratesmentioning
confidence: 99%